The Contribution of the Study of the Near-Death Experience to the Christian Concept of Resurrection - Stephen Hosea Vongdip; Agai Matthew Jock (African Theological Journal for Church and Society)
The near-death experience (NDE) is argued to be strictly a feeling that the percipient regards as a reality, yet some say it is strictly a brain malfunction that allows visions of various images to be seen and stored in human memory. Percipients of the NDE have reported a feeling of separation from their physical bodies. They claim that there is a spiritual body in them that rises above, leaving their physical bodies behind during their near-death experiences. Christians have a fundamental belief that Jesus was resurrected from death with a physical body that was also spiritual or supra in nature, and they also believe that those who died in Christ shall be resurrected, but with what kind of body shall they be resurrected? The NDE is a pre-death experience while resurrection is a post-death experience. However, both experiences suggest the emanation of a unique or supra being from the body and, while resurrection encourages a reunification of the body and soul, the NDE encourages a separation between the body and the soul. The question regarding the nature of the resurrection body is the focus of this research. The researchers argue that the study of the NDE can contribute to elucidating the nature of the resurrection body. This research is literary and comparative in approach because the views of various authors are evaluated in the search to establish the connection between the resurrection body and the NDE supra body.